2022
DOI: 10.3390/en15207552
|View full text |Cite
|
Sign up to set email alerts
|

Energy Performance Certificate Classes Rating Methods Tested with Data: How Does the Application of Minimum Energy Performance Standards to Worst-Performing Buildings Affect Renovation Rates, Costs, Emissions, Energy Consumption?

Abstract: Energy renovations of the building stock are a paramount objective of the European Union (EU) to combat climate change. A tool for renovation progress monitoring is energy performance certificate (EPC) labelling. The present study tested the effect of different EPC label classifications on a national database, which comprises ~25,000 EPC values from apartment buildings, detached houses, office buildings, and educational, commercial, and service buildings. Analysing the EPC classes labelling resulting from four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This variation is particularly evident in the approach to energy performance assessment, with operational rating relying on actual energy use (measured) and/or asset rating based on assumed standard usage (calculated) [81]. Research by Semple and Jenkins (2020) [80] investigated EPC schemes in six countries, revealing how different methodologies can yield disparate conclusions about building stocks, while Ferrantelli and Kurnitski (2022) [82] found that EPCs issued using four distinct methodologies resulted varying, and at times unrealistic, renovation rates for Estonian building. These findings underscore the necessity for a standardized EPC energy labeling system.…”
Section: Epc Global Significance and Challengesmentioning
confidence: 99%
“…This variation is particularly evident in the approach to energy performance assessment, with operational rating relying on actual energy use (measured) and/or asset rating based on assumed standard usage (calculated) [81]. Research by Semple and Jenkins (2020) [80] investigated EPC schemes in six countries, revealing how different methodologies can yield disparate conclusions about building stocks, while Ferrantelli and Kurnitski (2022) [82] found that EPCs issued using four distinct methodologies resulted varying, and at times unrealistic, renovation rates for Estonian building. These findings underscore the necessity for a standardized EPC energy labeling system.…”
Section: Epc Global Significance and Challengesmentioning
confidence: 99%
“…The authors analyzed data from 2010 and found that the tax incentive policies failed to stimulate an increase in the minimum energy standards in residential buildings. Moreover, other authors have also explored the effects of fiscal and financial incentive policies on EPCs (e.g., Filippini et al [22]; Ferrantelli et al [63]; Neveu and Sherlock [64]; Ameer and Krarti, [65]; Shen et al [66]; Chen and Hong [67]; Alberini and Bigano [68]; Charlier [69]; and Dubois and Allacker, [70]). This literature review highlights the lack of consensus regarding the influence of fiscal and financial incentive policies on building energy efficiency.…”
Section: Existence Of Fiscal and Financial Incentive Policiesmentioning
confidence: 99%
“…The United States (U.S) Department of Energy (DoE) conducted a review of 22 LEED-certified buildings managed by the General Services Administration and discovered a 34% decrease in CO 2 emissions, along with a 25% reduction in energy consumption and an 11% decrease in water consumption [43]. Ferrantelli and Kurnitsk [46] analyzed various building types in Estonia. They found that eco-friendly buildings could reduce CO 2 emissions by at least 26% in educational buildings by 2030, based on a 24,898 Energy Performance Certificates (EPCs) database for Estonian buildings.…”
Section: Literature Reviewmentioning
confidence: 99%